2017
DOI: 10.5152/ucd.2017.3728
|View full text |Cite
|
Sign up to set email alerts
|

The role of surgeons on the development and performance of endoscopy

Abstract: 1Endoscopy is being frequently performed for both diagnostic and therapeutic applications in surgical practice. Surgery, as a scientific area, has an important role in the propagation of therapeutic endoscopic procedures. The contribution of surgeons to the evolution of endoscopic applications and its practice is a triggering factor for the improvement of endoscopic instruments and their widespread use.Training and education on basic diagnostic and therapeutic surgical endoscopy should be implemented as part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It was used to observe the rectal fistula by using a rectal speculum ( Fig. 1 ) [ [1] , [2] , [3] , [4] , [5] ]. The issue faced by this instrument was inadequate light and shallow depth of penetration; thus, Roman medicine produced a similar device and a three-bladed vaginal speculum discovered in the ruins of Pompeii (AD 70) [ 3 ].…”
Section: Historymentioning
confidence: 99%
“…It was used to observe the rectal fistula by using a rectal speculum ( Fig. 1 ) [ [1] , [2] , [3] , [4] , [5] ]. The issue faced by this instrument was inadequate light and shallow depth of penetration; thus, Roman medicine produced a similar device and a three-bladed vaginal speculum discovered in the ruins of Pompeii (AD 70) [ 3 ].…”
Section: Historymentioning
confidence: 99%
“…Education outcomes will be questionable if trainees are deprived of feedback on their performance (Dube & Rostom, 2016). When it comes to a large training group, the teaching burden on faculty members will be dramatically high (Dolay & Hasbahceci, 2017). Personal feedback also comes with inherited drawbacks, including inconsistency and bias (Nerup, Preisler, Svendsen, Svendsen, & Konge, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the overall prevalence of these procedural injuries among endoscopists ranges from 39% to 89% [ 9 , 10 ]. Endoscopy has become the most important and frequently performed procedure in gastroenterology [ 11 ]. Therefore, the injury risk is comparatively higher among physicians and surgeons involved in endoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%